A generalised stochastic volatility in mean VAR: An updated algorithm - Haroon Mumtaz (Queen Mary University of London, School of Economics and Finance, 2020)
In this note we present an updated algorithm to estimate the VAR with stochastic volatility proposed in Mumtaz (2018). The model is re-written so that some of the Metropolis Hastings steps are avoided.
Keywords: C3; C11; E3; 330; VAR; Stochastic volatility in mean; error covariance